Effects of one-time alternate-row deep fertilization on yield, quality, and nitrogen use efficiency in wheat following rice - Zhang, Yuting; Dun, Canping; Shi, Guanghui; Yan, Shijie; Yan, Lei; Zhao, Can; Zhang, Hongcheng; Wang, Weiling; Huo, Zhongyang (Frontiers in Plant Science, 2025)
IntroductionDeep placement technology has gradually become a key direction for simplified cultivation. However, few studies have explored the effects of different deep-band placement under the application of slow-release nitrogen fertilizer (SRNF) combined with urea on wheat yield and quality.MethodsIn this study, four treatments were designed: conventional split application of urea (CK), one-time broadcasting of SRNF combined with urea (M1), and two different one-time deep-band placement treatments of SRNF combined with urea (M2 and M3).ResultsThe results showed that compared with CK and M1, M2 could increase the nitrogen content in rhizosphere soil after the jointing stage, which in turn affected the activities of nitrogen assimilation enzymes and promoted nitrogen uptake and utilization in the aboveground parts of wheat. In addition, the M2 maintained a relatively high leaf area index and net photosynthetic rate, ultimately increasing the post-anthesis dry matter accumulation and laying a material foundation for yield improvement. The wheat yield under the M2 was significantly by 4.8% higher than that of the CK, which was mainly attributed to the increase in spike number and grains per spike. In contrast, M3 could maintain a stable yield while reducing grain protein content, thereby improving the quality of weak-gluten wheat.DiscussionThis study provides a theoretical basis and practical guidance for the development of deep fertilization technology for wheat following rice.